Improving the Image of Local Government with Leadership Communication Strategies: A Review of Karawang Protocol - Nugroho, Angga Septiano; Kusumaningrum, Rastri; Muslimah, Tikka (Neo Journal of economy and social humanities, 2025)
In the relationship between government and society, public trust in government agencies is needed. The image of the local government is a factor, as a public service organization the image affects the opinions circulating in the community. The preparation of this research, using qualitative research methods, with descriptive research design. Researchers used data collection methods through participant observation. In every activity agenda carried out by Regional Leaders, in this case the Regent of Karawang is certainly accompanied by the Protocol Team as a coordination and communication team in the field. In the implementation of the communication strategy carried out there are several stages, namely: 1. Activity Schedule Sharing, 2. Activity Data & Information Collection, 3. Observation, 4. Publication. Obstacles in implementation often occur, there are 3 factors that affect obstacles, namely, data, coordination & communication, and information delays. It can be concluded that, the image of the local government is very important in building public trust in government institutions, effective communication from local leaders, especially through the protocol team, plays a major role in improving the image of the government. The obstacles experienced certainly need to be overcome for the effectiveness of the communication strategy carried out, with the aim of improving the image of the Karawang Regency local government.